Vehicle collision with bridge piers: A state-of-the-art review. Issue 2 (January 2021) - Chen, Lin; Wu, Hao; Liu, Tao
Although the probability of vehicle collision with bridge piers is relatively low, it may cause the pier to fracture and even the entire bridge to collapse, resulting in casualties and huge economic losses. Therefore, bridge piers should be properly designed against vehicle collision. This paper aims to make a state-of-the-art review of the research on vehicle collision with bridge piers, to summarize the achievements and current limitations in this field, and to give some suggestions for future research. It is organized within a framework of performance-based design, which is divided into four types of problems, that is, hazard analysis, structural analysis, damage analysis, and loss analysis. Studies show that reinforced concrete (RC) piers under vehicle impact generally exhibit three damage modes, that is, local damage, shear damage, and flexural damage. When a large truck hits a pier, the engine and container (cargo) may contribute to a two-stage impact characteristic, which has a great influence on the response and damage of the pier. The vehicular impact (force) models and nonlinear response models of RC members under impact loads have been developed respectively, which can be combined to quickly analyze the nonlinear response of RC piers under vehicle impact. Deformation-based methods should be developed to quantify the damage level of RC piers under different damage modes. Current codes still mainly adopt the equivalent static force design method, but some provisions regarding probabilistic (reliability) analysis have appeared. More attention should be paid to the statistical analysis of roadside crashes and vehicle-related parameters in order to obtain a more realistic probabilistic analysis model, and further establish a performance-based design method for RC piers subjected to vehicle collision.